Exit Creek Transect Survey, June 2013 - Curran, Janet H. (ORCID: 000-0002-3899-6275); Williams, Haley B. (USGS Science Data Catalog, 2017)
This dataset consists of survey data from transects surveyed June 10-12, 2013 along Exit Creek, a stream draining Exit Glacier in Kenai Fjords National Park, Alaska. The survey was conducted using Global Positioning System Real-Time Kinetic (GPS-RTK) transceivers and tied to monuments previously established by the U.S. Forest Service. This survey repeated points from an initial (2011) survey of Transects 2 and 3 by the U.S. Forest Service and established Transects 4-7. The intent of the survey transects is to monitor changes in elevation across the braid plain of Exit Creek.